Acceptance towards internet banking by ASNB investors in Klang Valley / Mohd Firdaus Mohamad Arshad - Mohamad Arshad, Mohd Firdaus (Faculty of Business and Management, 2010)
The explosion of Internet usage and the huge funding initiatives in electronic banking have drawn the attention of researchers towards online banking. In the past, the conventional focus of online banking research has been on technological development, but this is now shifting to user-focused research. The purpose of this research is to identify the factors that influence the acceptance of online banking by the users and to identify the most common transaction by using online banking services. According to the technology acceptance model (TAM), perceived ease of use and perceived usefulness constructs are believed to be fundamental in determining the acceptance and use of various information technologies (IT). About 50 of questionnaires were distributed by hand to selected ASNB agent’s area in Klang Valley. The research findings show that the most factors influenced the acceptance of internet banking transaction among the ASNB investors was Online Banking Website Information. The respondents were strongly agree that clear and comprehensible instructions in the website were important and influenced their acceptances of using the internet banking. Besides, the findings show that the most common factors that have a second higher mean are Online Banking Usefulness. As a conclusion, the results of the findings that include the analysis of the demographic profile, general information of ASNB and the most factors that influence acceptance towards internet banking by ASNB investors. For the recommendation of this study made based on several logical factors and impact of current situation to the acceptance of the ASNB investors towards the internet banking. The research constructs were developed based on the Technology Acceptance Model and incorporated two additional elements of privacy and security and online banking website information.